The interrelated transmission of HIV-1 and cytomegalovirus during gestation and delivery in the offspring of HIV-infected mothers - Khamduang W. (2014)
Our objective was to analyze, in formula-fed infants, correlates of HIV mother-to-child transmission, including cytomegalovirus (CMV) infection. HIV-infected infants were matched with HIV uninfected by maternal HIV RNA in a case-control design. Infant CMV infection was determined by CMV IgG at 18 months and timed by earlier CMV IgM or CMV DNA. Correlations were assessed using logistic regression. In utero HIV infection was independently associated with congenital CMV infection (P = 0.01), intrapartum HIV infection with congenital-plus-intrapartum/neonatal CMV infection (P = 0.01), and overall HIV with overall CMV infection (P = 0.001), and prematurity (P = 0.004). Congenital and acquired CMV infections are strong independent correlates of mother-to-child HIV transmission. © 2011 by Lippincott Williams & Wilkins.